Pre-Service Teachers with Courses in Problem-Based Learning in Mathematics - Hasbi, Muhammad; Fitri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
Study This aim is to determine the effectiveness of the application of the problem-based learning model in learning statistical material for lower-level students. This research was conducted at the As'adiyah Sengkang Islamic Institute. Data collection techniques used are test results studies, sheets of observation activity, and questionnaire responses by students. The results show that: (1) the average score of the results study statistics student before the problem-based learning model is applied is 25.41 and is in the very low category with a standard deviation of 9,688. From the results obtained, 37 students, or 100%, did not reach completeness. Meanwhile, the average score of the results of the study statistics for students after the PBL model is applied is 8.3, with a standard deviation of 9,036. From the results obtained, 35 students, or 9.60%, reached completeness as individuals, and 2 students, or 5.40%, did not reach completeness as individuals. (2) Activity students are in the category of good. (3) Questionnaire responses from students show that responses are positive. (4) Average implementation of learning in the PBL model, which is 3.73, and this means we are in the category accomplished with ok. Based on the results of the study, it can be concluded that the application of the problem-based learning model is effective in teaching statistics to students at the Sengkang As'adiyah Institute of Islamic Religion.